PENGARUH E-COMMERCE TERHADAP PENURUNAN KUNJUNGAN KONSUMEN DI PASAR TRADISIONAL PUD KOTA MEDAN - Juanta, Palma; Agitha Kembaren, Eykel; Jery Alfa Hutabarat, Bendedict; Saga Mo Lewio Dachi, Theodorus; Sumantri, Akbar; Efrat Freditus Tampubolon, Mertfil (ADIDAYA : Aplikasi Pendidikan dan Sosial Budaya, 2025)
The development of digital technology has significantly changed consumer shopping behavior, especially through the emergence of e-commerce platforms that offer convenience, speed, and efficiency. This phenomenon has directly impacted traditional markets, which are experiencing a decline in consumer visits. This study aims to analyze the influence of e-commerce development on the intensity of consumer visits to traditional markets under the management of PUD Pasar Kota Medan. A quantitative approach was employed through a survey method, where data were collected using questionnaires distributed to active consumers who have shopped at traditional markets. The instruments used were tested for validity and reliability. The data were analyzed using descriptive and inferential statistical techniques, including normality tests, homogeneity tests, and t-tests. The results revealed a significant effect of e-commerce on decreasing visit intensity, as indicated by a significance value of 0.004 (< 0.05). This finding indicates that the accessibility, product variety, and digital promotions offered by e-commerce platforms influence changes in consumer shopping preferences. This study contributes to understanding the shift in consumer behavior in the digital era and serves as a reference for traditional market managers and local governments in designing adaptive and innovative digital strategies to maintain the competitiveness of traditional markets.